The Development of Agriculture in Agricultural Areas of Siberia: Multifunctional Character, Environmental Aspects - KOSENCHUK, Olga; SHUMAKOVA, Oksana; ZINICH, Alla; SHELKOVNIKOV, Sergey; POLTARYKHIN, Andrey (Journal of Environmental Management and Tourism; Vol 10 No 5 (2019): JEMT Volume X Issue 5(37) Fall 2019DO - 10.14505//jemt.v10.5(37).06, 2019)
In today's conditions, the problem of reviving the village is becoming increasingly acute in order to improve the level and quality of life of the local population and ensure the country's food security. The main goal of the research is to identify possible directions for the development of agrarian territories on the basis of multifunctionality and diversification of the rural economy. The article contains a brief theoretical analysis of the concept of “multifunctional agriculture” in relation to agricultural territories based on domestic and foreign practice, and the functions performed by agriculture are established. The current level of socio-economic development of agriculture in Siberia is assessed. The features of its development are disclosed, the influence of the multifunctional nature of agriculture on the development of agricultural territories is determined. To determine the promising areas of rural development, the potential of agrarian territories in the development of sources and opportunities for the economic activity of the population has been identified, and the need to diversify the agricultural sector of the Siberian economy as the basis for the development of multifunctional agriculture in conditions of economic instability has been proved. Within the framework of the study, for the realization of the ecological, social and economic functions of agriculture on the basis of diversification of the rural economy, promising directions for the development of agrarian territories have been proposed that can speed up the recovery of the rural economy of Siberia.